PO220 Cutting out cutting needles for lumbar puncture: lessons learnt from clinical practice, audit and delivery of an atraumatic needle lumbar puncture workshop to trainee doctors at chelsea and westminster hospital. (1st December 2017) - Crawshaw, Ania; Salman, Marwa; Dob, Daryl; Kennedy, Angus; Janssen, John; Davies, Nicholas
Abstract : Compared with cutting needles, use of atraumatic pencil-point needles significantly reduces incidence of post-lumbar puncture headache. Many physicians still use cutting needles for lumbar puncture (LP), despite the comparatively higher morbidity and consequent monetary cost. Clinical Case: A patient underwent diagnostic lumbar punctures with a cutting needle. The resulting CSF leak identified on MRI required treatment with a blood patch. Following this procedure, he developed a severe systemic inflammatory response. These complications prolonged his admission by 4 weeks. Audit: We audited ward and daycare stock of spinal needles in our Trust, and surveyed local junior doctors regarding their knowledge and experience of different needles for lumbar puncture. Results: 87% of stocked needles were cutting needles. 76% of trainees surveyed knew no differences between atraumatic and cutting needles and only 8% had used atraumatic needles before. Action: A series of LP workshops were delivered to trainees. Benefits of atraumatic needles were explained and LP technique using atraumatic needles was taught on a manikin. Conclusions: Due to the rotational nature of doctors' training, the atraumatic needles LP workshop will need to be delivered again at regular intervals in the future. Other Trusts would benefit from developing similar training sessions.